ANALISIS NERACA KASUS PEMBERIAN DANA TALANGAN (BAILOUT) BANK CENTURY - Widita Kurniasari (Universitas Trunojoyo Madura, 2012)
The Bank Century takeover by the Deposit Insurance Corporation was due to the Capital Adequancy Ratio (CAR) of its 2008 balance sheet was negative so that it was needed to raise additional capital to be 8% according to CAR eligibility as required by Bank Indonesia. The December balance sheet of 2007 and 2008 exposed that CAR, ROA, ROE, NIM, assets, and deposits of Bank Century were negative. This indicates that the bank was inefficient, it did not gain any return from its investments and even more it suffered losses.